Decision-making deficits in obsessive-compulsive disorder are associated with abnormality of recency and response consistency parameter in prospect valence learning model - Murayama, Keitaro; Tomiyama, Hirofumi; Ohno, Aikana; Kato, Kenta; Matsuo, Akira; Hasuzawa, Suguru; Sashikata, Kenta; Kang, Mingi; Nakao, Tomohiro (Frontiers in Psychiatry, 2023)
Background: Patients with obsessive-compulsive disorder (OCD) have deficits in decision-making in the Iowa Gambling Task (IGT). However, no study has investigated the parameters of the prospect valence learning (PVL) model in the IGT for OCD.Aims: This study aimed to investigate deficits in decision-making in OCD using the PVL model and to identify whether the parameters of the PVL model were associated with obsessive-compulsive severity.Methods: Forty-seven medication-free patients with OCD were compared with 47 healthy control subjects (HCs). Decision-making was measured using the total net and block net scores of the IGT. A PVL model with a decay reinforcement learning rule (PVL-DecayRI) was used to investigate the parameters of the model. Correlation analysis was conducted between each parameter of the PVL-DecayRL and obsessive-compulsive symptoms.The total net score of patients with OCD was significantly lower than that of the HCs. The block net scores of the OCD group did not differ across Decision-Making Deficits in OCD 3 the five blocks, whereas in the HCs, the fifth block net score was significantly higher than the block net scores of the first and second blocks. The values of the recency and response consistency parameters of the PVL-DecayRI in patients with OCD were significantly lower than those in HCs. The recency parameter positively correlated with the Y-BOCS obsessive score. Meanwhile, there was no correlation between consistency parameter values and symptom severity in OCD.Our detailed analysis of the decision-making deficit in OCD suggests that the most recent outcome has a small influence on the expectancy of prospect valence, as indicated by the lower recency parameter, and is instead characterized by more impulsive choices, as indicated by the lower consistency parameter.